An insight into the biomechanics of twisting - Fink, H. (Technique, 1997)
An understanding of how a gymnast twists in the air is still not complete, even in the mind of physicists and mathematicians; however, the past decade has seen much progress in identifying which of these mechanisms are most effective or contributory to successful twisting. A major problem has been that, although the human body must obey the laws of physics, it does not act as a rigid system and therefore is not easily analyzed. In fact, a recent survey (Frohlich, 1979) of the 59 physicists who responded to a questionnaire, more than 56% believed that a somersaulting diver could not initiate a twist having left the board; something practitioners have known to be readily possible for some time. Ten years earlier a paper was published (Leigh & Bengerter 1967) which attempted, with the use of cinematography, to demonstrate that coaches were poorly prepared in basic theory because all in the study believed (probably correctly) their divers and trampolinists to have initiated their twists in the air, contrary to what the authors believed the film to show. The reasons for past difficulties are not hard to understand. All "knew" that according to the principle of conservation of angular momentum, rotation could not be initiated in the absence of an applied torque. Also until the late 1960s not many aerial performances in the sense of multiple somersaults with delayed multiple twists had been seen; the common appearance of which finally did challenge theoreticians to explain. Finally it may well be, and the issue is far from resolved, that as many as three or four twisting mechanisms are active during one performance and that these mechanisms may interact throughout a complicated twisting and somersaulting performance.